Usulan Perbaikan Proses Pelayanan Loading dan Unloading Kapal di Dermaga Curah Cair PT. X dengan Pendekatan Simulasi - Misra Hartati; Irham Hamzah Zah; Fitra Lestari Norhiza; Tengku Nurainun (Universitas Katolik Parahyangan, 2019)
Indonesia as one of the biggest archipelagic countries, sees the potential for the need for ports as an inter-island logistics sector. Ports in Indonesia are managed by PT. Indonesian Port, one of the branches of PT. Pelindo is PT. X which has liquid bulk stores specifically for CPO loading and unloading. The problem that occurs is the increase in loading and unloading service time that has exceeded the set resting time, which results in the length of the waiting time for the ship in the pool. So that it will have an impact on the quality of CPO, which causes an increase in the levels of free fatty acids in CPO. Because it is proposed to improve the process of loading and unloading CPO services to minimize queues and reduce ship waiting times. Simulation is completed with ExtandSim software. As for the selected scenario, namely the second alternative scenario showing an increase in service on each pier, the average ship input is 64 ships and the average output is 62 ships, more optimal than conceptual conditions, the proposed calculation of investment costs is the addition of a pipeline of 104,244.00 US .Keywords: Extendsim, Port Of Liquid Bulk, CPO, Descrette Event Simulation